The functional significance of E277K and V295A HFE mutations - Silva, Bruno (2012)
Hereditary haemochromatosis (HH) is an autosomal recessive disorder characterized by excessive intestinal iron absorption resulting in increased pathological body iron stores. It is typically associated with homozygosity for the c.845G>A (p.C282Y) mutation in the HFE gene. However, other HFE alterations have been reported in affected individuals but their association with the disease is unclear. This study analysed the functional consequences of two HFE mutations, c.829G>A (p.E277K) and c.884T>C(p.V295A). Firstly, it was shown that c.829G>A affects the HFE splicing by diminishing the full length HFE and ivs4_66bp inclusion transcript levels, while increasing the amount of exon 4 skipping transcript. Immunofluorescent techniques showed that the HFE_E277K protein had a diffuse distribution(similar to HFE_C282Y) while HFE_V295A presented at the cell surface and perinuclear compartments (resembling HFE_wt). Immunoprecipitation assays revealed a decreased association of HFE_E277K and HFE_V295A with both b2-microglobulin (B2M; 38 ± 7% and 66 ± 8%, respectively) and transferrin receptor (TFRC, also termed TFR1) (58 ± 2% and 49 ± 16%, respectively). Herein, we prove that both mutations partially abrogate HFE association with B2M and TFRC, crucial for its correct processing and cell surface presentation. Although E277K has a more deleterious effect than V295A, we propose that both mutations may play a role in the development of hereditary haemochromatosis.